Microstructural and Micromechanical Effects of Cold Roll-forming on High Strength Dual Phase Steels - Meritxell Ruiz-Andres; Ana Conde; Juan de Damborenea; Ignacio Garcia (Materials Research, 2015)
In this work correlation between the 1000 MPa dual phase (DP) steel microstructure and the strain gained after roll-forming process have been studied by both microstructural and micromechanical analysis. The scanning electron microscope (SEM) inspection in the bent area reveals changes in the ferrite-martensitic microstructure. The plastic deformation of DP steels originates defects at the edges of bent sheet make them partly responsible for the damage caused. In addition, electron backscatter diffraction (EBSD) measurements have been carried out for an in-depth characterization after roll-forming. A high density of misorientation of the crystal lattice within the ferrite strained grains is observed, mainly concentrated in the ferrite/martensite grain boundaries. Furthermore, the ultramicrohardness tests exhibit little dependence between mechanical parameters and the material properties.